ANALISIS MOTIVASI SISWA DALAM MENGIKUTI EKSTRAKURIKULER BULUTANGKIS - Nana Suryana Nasution; Fauzi, Dira; Sumarno, Ardawi; Hindawan, Ilham (Universitas Muhammadiyah Kuningan, 2024)
This study aims to analyze how much motivation students have in participating in Badminton extracurricular activities at MAN 3 Karwang but also to find out how much intrinsic motivation and extrinsic motivation students have in participating in Badminton extracurricular activities at MAN 3 Karawang. Research is quantitative descriptive research using survey methods, with data collection techniques using instruments in the form of questionnaires in the form of questionnaires. For the population in this study, there were 32 students who took part in extracurricular Badminton at MAN 3 Karawang. The instrument used was in the form of a questionnaire totaling 35 questions. Data analysis is used descriptive statistical analysis with the level of achievement of respondents. The results showed that students' motivation in participating in extracurricular Badminton at MAN 3 Karawang obtained overall can be categorized as medium with a respondent achievement level of 79.69%. While the intrinsic motivation factor obtained the results of the respondent's achievement level of 84.59% with the high category and for extrinsic motivation factors obtained the results of the respondent's achievement level of 74.79% with the medium category.